Identifikasi Potensi Interaksi Antibiotik pada Resep di Salah Satu Apotek Kota Bandung Bulan Desember 2024 - Kirana Fayruz Swarga; Ferry Ferdiansyah Sofian; Ina Siti Sholihah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study aims to identify and analyze potential antibiotic drug interactions in prescriptions collected from a pharmacy in Bandung during December 2024. A total of 215 prescriptions containing antibiotics were examined, revealing 8 cases of drug interactions, all involving ciprofloxacin. The interactions ranged from minor to major severity levels, with major interactions primarily associated with corticosteroids such as methylprednisolone and dexamethasone. These findings highlight the high interaction potential of ciprofloxacin compared to other antibiotics. The study emphasizes the importance of careful prescribing practices, thorough medication history review, and healthcare provider education to minimize adverse drug reactions. Strengthening drug interaction monitoring systems is crucial to improving patient safety and treatment outcomes.